Starch fraction profiles of milled, nonparboiled rice varieties from Nigeria - Odenigbo, A.M.; Ngadi, M.; Manful, J.; Danbaba, N. (Wiley, 2013)
This study determined the levels of nutritionally important starch fractions in selected milled, nonparboiled rice cultivated in Nigeria. Five improved varieties (FARO 52, FARO 57, FARO 44, FARO 60 and FARO 61) and four local varieties (Kwandala, Yardass, Jeep and Jamila) were evaluated. There were significant differences in starch fractions among varieties. Resistant starch (RS) ranged between 1.43% and 3.13%. Rapidly digestible starch (RDS) was lowest in Jamila (27.70%) and highest in FARO 61 (39.26%). Generally, the local varieties had significant higher RS (2.71%) with a lower RDS (32.82%) compared with improved varieties (RS; 1.88% and RDS; 36.07%). RS was inversely related to RDS and starch digestion index (SDI). The SDI had a highly significant positive correlation with RDS (r = 0.879, P < 0.01). These results highlight the need for further work in the identification of milled, nonparboiled rice varieties with less rapid digestion for its associated health benefits to consumers.